Auditory brainstem response to level-specific CE-CHIRP® threshold estimation in normal-hearing adults - Dzulkarnain, Ahmad Aidil Arafat; Ahmad Shuckri, Suhaila; Ismail, Noraidah (Wolters Kluwer Medknow Publications, 2021)
: The aim of the present study was to compare the hearing thresholds between pure tone audiometry (PTA) and auditory brainstem response (ABR) from level-specefic (LS) CE-Chirp and click stimuli in normal adult subjects. Material and methods: twenty-four adults with auditory thersholds using both the LS CE-Chirp and click stimuli,Study Design and Statistical Analysis: A quasi-experimental study from both stimuli were compared using the Friedman test with Wilcoxon signed-rank test as the post hoc analysis. Result : No statiscally median thresholds differences were indentified betweeen the PTA and the ABR to LS CE Chirp thresholds at LFs and only small differences(<6 dB) compared to the ABR from the click stimulus. Conclusion: This study concluded that the ABR to LS CE-Chirp® has closer thresholds than the ABR to LS CE-Chirp has closer tresholds than the audiogram.